2014
DOI: 10.1371/journal.pone.0086975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Optimal Daily Fertigation on Migration of Water and Salt in Soil, Root Growth and Fruit Yield of Cucumber (Cucumis sativus L.) in Solar-Greenhouse

Abstract: Inappropriate and excessive irrigation and fertilization have led to the predominant decline of crop yields, and water and fertilizer use efficiency in intensive vegetable production systems in China. For many vegetables, fertigation can be applied daily according to the actual water and nutrient requirement of crops. A greenhouse study was therefore conducted to investigate the effect of daily fertigation on migration of water and salt in soil, and root growth and fruit yield of cucumber. The treatments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
5
35
0
7
Order By: Relevance
“…Chand (2014) also reported that increasing fertigation levels showed almost equal yield. Similar results are reported by Abdrabbo et al, (2005); Guler et al, (2006); Amer et al, (2009);Kapoor et al, (2013);Feleafel et al, (2014); Liang et al, (2014) and Tekale et al, (2014). The yield in all the treatments was higher as compared to farmers' practice (4.47 kg m -2 ).…”
Section: Marketable Yieldsupporting
confidence: 87%
“…Chand (2014) also reported that increasing fertigation levels showed almost equal yield. Similar results are reported by Abdrabbo et al, (2005); Guler et al, (2006); Amer et al, (2009);Kapoor et al, (2013);Feleafel et al, (2014); Liang et al, (2014) and Tekale et al, (2014). The yield in all the treatments was higher as compared to farmers' practice (4.47 kg m -2 ).…”
Section: Marketable Yieldsupporting
confidence: 87%
“…The reduction of the water depletion period in the soil is beneficial for the development of the crop (Araújo et al, 2012). Further to this, daily irrigation maintains relatively stable soil moisture, which results in an increase in the emission of fine roots and cucumber crop growth (Liang et al, 2014). However, it would be more suitable to analyse the benefits of maintaining the moisture levels while taking into account the times of greatest transpiration demand.…”
Section: Discussionmentioning
confidence: 99%
“…The root absorption can be regulated by adjusting the volume and nutrient composition of the feed (Ho & Adams 1994). Conversely, the 78 H. Li and Z. Cheng assimilation and accumulation of nutrients provide material basis for root growth and vitality (Liang et al 2014). It was confirmed that the restricted root growth may impose negative effect on carbohydrate metabolism and whole growth of cucumber (Robbins & Pharr 1988).…”
Section: Treatmentmentioning
confidence: 96%